A scFv antibody fragment as a therapeutic candidate to neutralize a broad diversity of human IFN-alpha subtypes - Depetris, M. (2008)
Despite their significant role in maintaining the normal physiology, cytokines may cause pathological conditions when they are overproduced. In this way, the increased expression of human interferon alpha (hIFN-α) is associated with acute viral infections, inflammatory disorders and several autoimmune illnesses, where the cytokine may be a factor in either initiating or maintaining the disease. Currently, there are several mAbs marketed for a variety of indications and many more in clinical trials, in which IFN-α represents a potential target for antibody-based therapy. A panel of 11 murine mAbs was prepared using recombinant hIFN-α2b as immunogen, all of which bound to the native form of the cytokine with affinity constants ranging from 1.7 × 107 M- 1 to 1.4 × 1010 M- 1. An epitope mapping protocol demonstrated four spatially distinct areas of the protein recognized by the mAbs. Taking into account the characterization of the antibodies and their ability to inhibit the IFN-α biological activity, four mAbs were selected to produce scFv fragments. One of these fragments (CA5E6) was able to neutralize a wide spectrum of subtypes of the IFN-α family, including the recombinant cytokines hIFN-α2a and hIFN-α2b and a heterogeneous collection of IFN-α produced by activated leukocytes and Namalwa cells. With the aim of improving the affinity of the selected fragment, a standard error-prone PCR method was carried out. By using this strategy, it was possible to generate a new fragment (EP18) with increased affinity and ability to neutralize a broad diversity of IFN-α subtypes. Consequently, the scFv EP18 represents a potential therapeutic agent for those immune and inflammatory diseases which are associated with an increased IFN-α expression.